A Comparison between Analytical and Numerical Solution of the Krogh's Tissue Cylinder Model for Human Bone Marrow (Journal of Chemical Engineering, 2010)
The Danish physiologist, August Krogh is the founder of the theory of oxygen transport to tissues. It washis famous tissue cylinder model developed for skeletal muscle, together with his colleague mathematicianErlang that laid down the foundation of the mathematical modeling of oxygen transport to tissues. Here ananalytical solution of the Krogh’s model has been presented based on justifiable assumptions in order tovalidate the numerical approach used to solve more realistic oxygen transport models. The numericalsolution of Krogh’s model is performed using computational fluid dynamics (CFD) software CFX 4.4.From the analytical solution, it is demonstrated that variation from the numerical result is less than 0.2%which in turn justifies the use of computer software in developing mathematical model for suchphysiological systems like BM.Journal of Chemical Engineering Vol.ChE 24 2006 1-6